Experimental study of the impact of process variation on Internal Latchup (ILU) in 130nm technologies and statistical data analysis for performance optimization - Brijesh Mayurkumar Shah (Nanyang Technological University, 2023)
Semiconductor devices are the backbone of the technological revolution. There would be no digital devices without a chip. As such it is important to identify the root of device failures, such that they can be worked on to come up with the solution. When semiconductor devices were first invented, one of the issues was latchup. Latchup is an issue which can cause a device to be permanently damaged. Many solutions have been found since latchup was discovered as an issue. With the various solutions offered, it is imperative that we know whether the solutions can be paired together to further improve working efficiency. Furthermore, with frequent advancements in technology it is important to review traditional solutions to ensure that they are still as effective. GlobalFoundries is a multinational semiconductor manufacturing company developing technology for a wide range of products, from Smart Mobile Devices to Datacenter Infrastructure. As such the company strives to innovate and improve technology. This project will focus the dependance of devices on Ltap, as well as ascertain if traditional solutions still have the same expected impact. This will be done through vigorous internal latchup testing across various devices with slight differences in designs. Through the analysis of data we can understand the working of the devices better and they will help lay the path for future work in developing devices with higher device density without compromising on latchup robustness.